How a school milk program is fighting hunger in Yemen | From fragility to stability - Goldberg, Mark Leon; Qasem, Adeeb; Bliznashka, Lilia (Global Dispatches, 2024)
Today’s episode is produced in partnership with the CGIAR Research Initiative on Fragility, Conflict, and Migration for a series that examines what works to improve the well-being of people in Fragile and Conflict-Affected Settings. CGIAR is a global partnership that unites international organizations engaged in research about food security.